Change in indirect U.S. dependence on the PRC over the 2017–2023 period due to increased trade and manufacturing relations with Vietnam - Kon’ I.R. (Восточная Азия: факты и аналитика)
The fragmentation of the world economy and the associated reconfiguration of global production networks have been discussed in academic and business literature for a relatively long time, but the topic of the division of the world into geopolitically determined trade and production blocs has received the most attention in the last 7 years, since the beginning of the trade confrontation between the US and the PRC. This study focuses on quantifying the change in the US indirect dependence on the PRC over the period from 2017 to 2023 due to the US government-initiated process of increasing trade and production ties with Vietnam (friendshoring). The change in indirect dependence refers to the change in the share of value added of a geopolitical adversary country in the structure of value-added exports of a geopolitical ally or neutral country to the initiating country of friendshoring. The information base of the study is the latest multiregional input-output tables released by the Asian Development Bank in 2024, based on which the value-added structure of Vietnam's exports to the US for 2015–2023 was calculated. The findings show an increase in the indirect dependence of the US on the PRC, expressed in the increase in the share of Chinese value added in Vietnam's exports to the US, over 2017–2023 by 4.5 p. p., but there is а sectoral and temporal specificity. The share of Chinese value- added in Vietnam's exports was highest in 2021, and among the top five sectors of the Vietnamese economy in terms of absolute increase in exports to the US, the increase in Chinese value-added share in their exports is the highest in the only high-tech sector among them. Consistent factors that may have influenced the increasing share of Chinese value-added in Vietnamese exports to the US are suggested. Among them are spatial proximity, economic differences in the level of development between Vietnam and the PRC, and socio-cultural ties.